SPATA2 and CYLD inhibit T cell infiltration into colorectal cancer via regulation of IFN-γ/STAT1 axis - Tan, Tze Guan; Zybina, Yulia; McKenna, Cooper; Olow, Aleksandra; Rukmini, Subhadra Jayaraman; Wong, Michael Thomas; Sadekova, Svetlana; Chackerian, Alissa; Bauché, David (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is largely refractory to currently available immunotherapies such as blockade of programmed cell death protein-1 (PD-1). In this study, we identified SPATA2 and its protein partner CYLD as novel regulators of CXC-ligand 10 (CXCL10), a T-cell-attractant chemokine, in CRC. By specifically deleting SPATA2 and CYLD in human and mouse CRC cell lines, we showed that these two proteins inhibit STAT1 accumulation and activation and subsequently CXCL10 expression in tumor cells. At steady-state, STAT1 is highly ubiquitinated in a SPATA2/CYLD-dependent manner. Finally, we demonstrated that tumor-specific deletion of SPATA2 and CYLD enhances anti-PD-1 response in vivo. Our data suggest that SPATA2 and CYLD represent two potential novel targets for treatment of immune-excluded, PD-1-resistant tumors.